Pharmacological Maintenance Treatment for Alcohol Dependence - Vasiknanonte, Sorayut (Journal of the Psychiatric Association of Thailand, 2013)
Abstract Alcohol dependence and alcohol abuse are common illnesses. They are usually comorbid with medical and/or other psychiatric illnesses and lead to work, economic, family and social problems. Treatment for alcohol dependence usually starts with the detoxification phase but the more important phase is maintenance and long term treatment to prevent a relapse. At present, the US FDA only approves disulfiram, naltrexone and acamprosate for maintenance treatment. The pharmacological action of disulfiram has adverse effects which occur when a patient drinks any alcohol, resulting in most patients not complying with long-term use of disulfiram. Naltrexone and acamprosate are not marketed in Thailand. Some SSRIs may reduced the alcohol consumption in some sub-groups of alcohol dependence patients, who also have depressive illness. Ondansetron may be more effective with early onset type of alcohol dependence. Antiepileptics such as carbamazepine, oxcarbazepine, valproate, gabapentin, topiramate and GABA receptor agonists such as baclofen show evidences from RCTs of the efficacy in reducing the relapse rate, craving, amount of alcohol consumption, the portion of heavy drinking day and an increase the portion of abstinence day. Some RCTs shown that topiramate and oxcarbazepine have a comparable efficacy with naltrexone. There are some recent evidences that the second generation antipsychotics, such as quetiapine and aripiprazole, are able to reduce alcohol consumption in alcohol dependence patients. From the evidence, all the medications above may be the alternative choice for the maintenance treatment for Thai alcoholic patients.